1982
DOI: 10.1111/j.1365-3040.1982.tb01245.x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the importance of ethanol in causing injury to flooded plants

Abstract: We have examined the widely held theory that ethanol toxicity is a prime cause of the injury and death of plants in soil flooded with water. The tests were made on peas {Pisum sativum L.) at the early flowering or fruiting stages, when they ar"e known to be severely injured by flooding.Supplying ethanol in aerobie or anaerobic nutrient solution at similar eoneentrations to those we found in flooded soil (up to 3.9 mol m"^) or in the xylem sap of flooded pea plants (up to 2.1 mol tn -^) caused no injury. One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0
4

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 49 publications
5
57
0
4
Order By: Relevance
“…germanica. The toxicity of ethanol to plant tissues has been questioned in a detailed review of this subject by Jackson, Herman and Goodenough (1982). However, in these studies the conclusions were based either on the effects of ethanol given under aerobic conditions or else to seedlings where even though the root medium was anaerobic there was ready access to oxygen by diffusion from the shoot.…”
Section: Resultsmentioning
confidence: 99%
“…germanica. The toxicity of ethanol to plant tissues has been questioned in a detailed review of this subject by Jackson, Herman and Goodenough (1982). However, in these studies the conclusions were based either on the effects of ethanol given under aerobic conditions or else to seedlings where even though the root medium was anaerobic there was ready access to oxygen by diffusion from the shoot.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol production in plants/fruits Ethanol production (through anaerobic metabolism) generally results from low concentrations of O 2 which can either be caused by reduced levels of external O 2 or due to enhanced resistance to the diffusion of O 2 into the plant parts/fruits (Jackson et al 1982). Fruits undergoing the developmental/ripening process exhibit changes in the levels of O 2 and CO 2 inside them.…”
Section: Ethanolmentioning
confidence: 99%
“…During ripening of fruit (Bufler and Bangerth 1982), 2. During anoxia (Jackson et al 1982), 3. Under few days of anaerobiosis (Kelly and Saltveit 1988), 4.…”
Section: Ethanolmentioning
confidence: 99%
“…In 1971, McManmon and Crawford (13) suggested that the diversification of the end products of fermentive metabolism could explain flooding tolerance in some species. Jackson et al (9) questioned whether ethanol itself could be responsible for anoxic injuries, but we (17,18) later demonstrated that ethanol can be toxic to specific plant systems even at concentrations comparable to those commonly found in plant tissues subjected to oxygen deficit.…”
mentioning
confidence: 99%